Challenges and Opportunities in Qualitative Research Sharing Young Scholars' Experiences - Tsang, Kwok Kuen; Liu, Dian; Hong, Yanbi (Springer Nature Singapore : Imprint: Springer, 2019)
This book shares young scholars' (current PhD students and those who completed their PhD between 2010 and 2015) experiences with conducting qualitative social research. Intended as a guide for newcomers to the field, it focuses on the practical issues encountered by qualitative researchers rather than methodological discussions. Accordingly, it addresses a range of representative issues in the qualitative research process - namely research design, data access, data collection, and data analysis - and covers a variety of social sciences topics.